Divergent synthesis of triazine dendrimers using a trimethylene-dipiperidine linker that increases efficiency, simplifies analysis, and improves product solubility - Mintzer, Meredith A. (2009)
To combine benefits stemming from the high nucleophilicity of piperidine and the flexibility afforded by aliphatic triamine linkers, a trimethylene-dipiperidine linker has been used to synthesize triazine dendrimers using a divergent route. The cyclic, secondary amine of the linker reacts with monochlorotriazine monomer units, 1, leading to a dendrimer growth strategy that requires two-steps-per-generation. This strategy reduces the number of steps required for synthesis by 50%. The new linker also reduces complexity in the NMR spectra because rotational isomerism observed in linkers with primary amines is not present. In addition, the final products contain no interior hydrogen-bond donating groups. The high solubility observed in organic solvents for protected dendrimers is attributed to this factor and the inherent flexibility provided by the linker. Gas phase simulation suggests that globular structure emerges after generation three, wherein the core of the dendrimer is effectively shielded from solvent.